Analysis of Retreatment Intention Influenced Quality of Service, Patient Trust, Healthy Culture, Dimediation of Patient Satisfaction at Betawi Hospital, North Jakarta - Moehammad Unggul Januarko; Nia Puspita Hapsari; Irwan Sofwan (Majalah Ilmiah Bijak, 2023)
The research problem is that there is a decrease in patient repeat visits in 2021, from the results of pre-research it was found that the decrease in visits came from a decrease in patient confidence, a healthy culture, decreased service quality, patients were dissatisfied with treatment. The intention of this study was to examine the influence of the measurement of marketing quality, healthy culture, patient trust, patient satisfaction and intention to revisit. This research is research quantitative, with a sample of 180 respondents consisting of 77 men and 103 women aged between 23-42 years. Respondents were taken by patients who had been treated twice. Analysis tool using SEM. The results showed that intention to repeat treatment was significantly influenced by patient satisfaction. Patient satisfaction has a significant effect on service quality, healthy culture and patient trust. Quality of service and patient trust directly have a significant effect on the intention to repeat treatment.